Dakwah Dalam Perspektif Al-Qur`an - Yuli Umro atin (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2020)
Abstract Da'wah is the activity of inviting or calling on humanity to be in the path of Allah SWT (religion), both through oral, written, or reasoning and deeds. In connection with the scope of the definition, from the Qur'an can be derived several terms, including: Da'wah al-Khair, tadhkir wa tanbih, tabsir wa tandhir, tabligh, tarbiyah wa ta'lim, Amar ma'ruf nahi munkar. From the term that is introduced by the Koran, if it is explored further it can be concluded that on the ideal ground in all the terms contained the message of transformation of the values ​​of goodness and truth and holiness that need to be upheld in life. This can be seen when the Koran talks about da'wah, then what must be preached is sabili rabbi 'or al-khair. When presenting tabligh, al-Qur'an describes the treatise, when exposing amar ma'ruf nahi munkar, the target is the upholding of ma'ruf when speaking tabar wa wa tandhir, the previous sentence spoke al-Haqq. In relation to preaching in the perspective of the Koran, the author wants to reveal more deeply and describe how the revelation of the verses about preaching in the Koran, and interpretation of the verses of preaching. The purpose of this research is to find out the revelation of verses about da'wah, the interpretation of verses of da'wah. This research is a library research, which is a study conducted in a library to analyze data and sources from a library, using the method of interpretation with the Maudhu's approach. Keywords: Da'wah, Perspective of the Qur'an Abstrak Dakwah adalah kegiatan mengundang atau menyerukan umat manusia untuk berada di jalan Allah SWT (agama), baik melalui lisan, tertulis, atau penalaran dan perbuatan. Sehubungan dengan ruang lingkup definisi, dari Al Qur'an dapat diturunkan beberapa istilah, termasuk: Dakwah al-Khair, tadhkir wa tanbih, tabsir wa tandhir, tabligh, tarbiyah wa ta'lim, Amar ma'ruf nahi Munkar.Dari istilah yang diperkenalkan oleh Al-Quran, jika dieksplorasi lebih lanjut dapat disimpulkan bahwa di tanah yang ideal dalam semua istilah terkandung pesan transformasi nilai-nilai kebaikan dan kebenaran serta kekudusan yang perlu dijunjung tinggi dalam kehidupan. Ini bisa dilihat ketika Alquran berbicara tentang dakwah, maka yang harus diberitakan adalah sabili rabbi 'atau al-khair. Ketika menyajikan tabligh, al-Qur'an menjelaskan risalah tersebut, ketika mengekspos amar ma'ruf nahi munkar, targetnya adalah menegakkan ma'ruf ketika berbicara tabar wa wa tandhir, kalimat sebelumnya berbicara al-Haqq.Sehubungan dengan dakwah dalam perspektif Alquran, penulis ingin mengungkapkan lebih dalam dan menggambarkan bagaimana wahyu ayat-ayat tentang dakwah dalam Alquran, dan interpretasi ayat-ayat dakwah. Tujuan dari penelitian ini adalah untuk mengetahui wahyu ayat-ayat tentang dakwah, penafsiran ayat-ayat dakwah. Penelitian ini adalah penelitian kepustakaan, yang merupakan penelitian yang dilakukan di perpustakaan untuk menganalisis data dan sumber-sumber dari perpustakaan, menggunakan metode interpretasi dengan pendekatan Maudhu. Kata kunci: Dakwah, Perspektif Al-Qur'an